Outpatient parenteral antibiotic therapy (OPAT) for the management of bronchiectasis - Jacky Tu; Mohammed Al Harasi; Michael Pallin; Chris Daley; Benjamin A. Rogers; Paul T. King (Heliyon, 2023)
Background: Patients with bronchiectasis often require hospitalisation for the administration of intravenous antibiotics for the management of acute exacerbations. Increasingly, Outpatient Parenteral Antibiotic Therapy (OPAT) services have become available as a potential alternative for domiciliary management. Aims: This study assessed outcomes in both cystic fibrosis (CF) and non-CF bronchiectasis patients who received OPAT for the management of an acute exacerbation of bronchiectasis. Methods: A retrospective study of consecutive subjects was done in both CF and non-CF groups in a large metropolitan Health Service in Australia from 2016 to 2022. Results: There were 51 episodes of care in the non-CF group (22 subjects) and 73 episodes in the CF group (13 subjects). The non-CF group were nearly all treated with once daily domiciliary intravenous (IV) ceftriaxone (49/51 episodes) for a duration of 9.1 ± 3.0 days (mean and standard deviation (SD)) via a peripherally inserted venous canula (84% of episodes). In contrast, the CF group generally received dual IV antibiotics (64% of episodes), with an average duration of 16.8 ± 6.3 days via central venous access (100%). In the non-CF group, the admission rate to hospital after 1 month was 9.6% and in the CF group was 0%. At 3 and 6 months the readmission rate for the non-CF group was 15.7% and 19.6% and CF group was 21.9% and 31.5%. There was a low rate of complications for the OPAT admissions (2% for the non-CF group and 7% for CF group). Conclusions: OPAT is a viable alternative for the management of bronchiectasis exacerbations.